Kompetensi Sikap Mahasiswa Terhadap Ketidakpatuhan Sipil Pada Kasus Penolakan UU Cipta Kerja - Tumpal Daniel (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2020)
Civil disobedience (Civil Disobidience) was getting stronger in the second period of the administration of Joko Widodo and Ma'ruf Amin. The movement of civil society can be monitored through conversations on social media to invite people to distrust the state's official institutions and policies. This was evident when there were demonstrations between workers and students over the ratification of the Job Creation Law. In fact, students who were initially only a sub-ordinance now seem to be pushed to become a determinant factor of emerging civil disobedience. The attitude of students rejecting the Job Creation Law is more influenced by social media and the knots of influence it follows. This study wanted to determine the relationship between student attitudinal competencies obtained from the KKNI-based college curriculum with the influence of social media on the rejection of the Job Creation Law so that students' tolerant attitudes towards civil disobedience were formed. The research method used is qualitative with tiered observations. Observations were made on a number of regulations and guidelines related to KKNI and SNPT, especially in the subject of Religious Education and Citizenship Education, as well as multilevel observations on hoax news spread on social media and the 8 October 2020 demonstration event along with a series of follow-up actions. The aim to be obtained is to find out how effective the learning outcomes of the course are for the formation of competency in attitudes and values ​​compared to the speed of information flow from the centers of influence that students receive in shaping their attitudes and behavior